Answer:
The equation of a polynomial of degree 3, with zeros 1, 2 and -1 is
![x^(3)-2 x^(2)-x+2=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1nhlnuwdsx0kqsjdz4sxu72atvdhnkkmbn.png)
Solution:
Given, the polynomial has degree 3 and roots as 1, 2, and -1. And f(0) = 2.
We have to find the equation of the above polynomial.
We know that, general equation of 3rd degree polynomial is
![F(x)=x^(3)-(a+b+c) x^(2)+(a b+b c+a c) x-a b c=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yybw7he0frqh374b510bew29mis14kih4r.png)
where a, b, c are roots of the polynomial.
Here in our problem, a = 1, b = 2, c = -1.
Substitute the above values in f(x)
![F(x)=x^(3)-(1+2+(-1)) x^(2)+(1 * 2+2(-1)+1(-1)) x-1 * 2 *(-1)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vciokxh9mbn5i9la0vh9w3yrpxvshweyxa.png)
![\begin{array}{l}{\rightarrow x^(3)-(3-1) x^(2)+(2-2-1) x-(-2)=0} \\ {\rightarrow x^(3)-(2) x^(2)+(-1) x-(-2)=0} \\ {\rightarrow x^(3)-2 x^(2)-x+2=0}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f4t9m8uw87yhhbkszxidzxuhng81b7t19e.png)
So, the equation is
![x^(3)-2 x^(2)-x+2=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1nhlnuwdsx0kqsjdz4sxu72atvdhnkkmbn.png)
Let us put x = 0 in f(x) to check whether our answer is correct or not.
![\mathrm{F}(0) \rightarrow 0^(3)-2(0)^(2)-0+2=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7frwvitl8o4c0kdm76qj951pphqnyttr0l.png)
Hence, the equation of the polynomial is
![x^(3)-2 x^(2)-x+2=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1nhlnuwdsx0kqsjdz4sxu72atvdhnkkmbn.png)